IDO Expression in Cancer: Different Compartment, Different Functionality? - Meireson, Annabel; Devos, Michael; Brochez, Lieve (Frontiers in Immunology, 2020)
Indoleamine 2,3-dioxygenase 1 (IDO1) is a cytosolic haem-containing enzyme involved in the degradation of tryptophan to kynurenine. Although initially thought to be solely implicated in the modulation of innate immune responses in infectious conditions, subsequent discoveries demonstrated IDO1 as a mechanism of acquired immune tolerance. In cancer IDO1 expression / activity has been observed in tumor cells as well as in the tumor-surrounding stroma which is composed of endothelial cells, immune cells, fibroblasts and mesenchymal cells. IDO expression / activity has also been reported in the peripheral blood. This manuscript reviews available data on IDO expression, mechanisms of its induction and its function in cancer for each of these compartments. In-depth study of the biological function of IDO1 according to the expressing (tumor) cell can help to understand if and when IDO1-inhibition can play a role in cancer therapy.